Normal and Malignant B-Cell - Aribi, Mourad (IntechOpen, 2020)
Normal and Malignant B-Cell is a collection of harmonious chapters contributed by different authors. This book sets out to describe the B-cell during different stages of ontogeny and the molecular mechanisms of its antigen receptor diversity. It also discusses the main clinical and etiopathogenic aspects when it is transformed into a malignant cell. The book will be interesting and useful for clinicians, biologists, researchers, teachers, and graduate students of both doctoral and master's degrees in the field of immunology.